Pengaruh Penerapan Pendekatan STEAM Terhadap Kemampuan Berpikir Kreatif Siswa Kelas IV SD - Atang Sutisna; Nova Aryanti; Dadang Cunandar (Universitas Muhammadiyah Kuningan, 2024)
The purpose of this study was to determine the effect of application the STEAM approach to students creative thinking ability in class IV SD Negeri 1 Jalaksana. The method in this research is Quasi Experiment Design with Nonequivalent Control Group Design. The research population was all students of class IV SD Negeri 1 Jalaksana totaling 57 students. The sample is class IV A as the control class totaling 29 students and class IV B as the experimental class totaling 28 students. The instruments in this study was a test of creative thinking skills in the form of a pre-test and post-test of 10 questions. The results show that learning with STEAM approach affect students creative thinking ability. This is evidenced by the obtained results of the hypothesis Sig. (2-tailed) = 0,000 < 0,05 and then H1 is accepted, which means that there is an effect of learning with the STEAM approach on students creative thinking ability in class IV SD Negeri 1 Jalaksana.